Equivalent Cellular and Humoral Immunity to Varicella Zoster Virus in Patients With Inflammatory Bowel Disease and Healthy Older Adults for Whom Immunization Is Recommended. Issue 1 (19th January 2022) - Caldera, Freddy; Wald, Arnold; Saha, Sumona; Smith, Ryan; McCrone, Sue; Farraye, Francis A.; Hayney, Mary S.
Abstract : INTRODUCTION: Patients with inflammatory bowel disease (IBD) are at an increased risk of herpes zoster (HZ). HZ is caused by reactivation of the varicella zoster virus (VZV) and is prevented by strong VZV-specific cell-mediated immunity. The aim of our study was to evaluate whether patients with IBD had lower or equivalent protection compared with healthy controls (HCs) at age 50 years and older. METHODS: We performed a cross-sectional study at a single academic center and evaluated cellular and humoral immunity to VZV in patients with IBD at age 35–49 years vs HCs aged 50–59 years. All patients with IBD were on stable medication regimens for at least 3 months. VZV-specific cell-mediated immunity was measured via ELISPOT, and humoral immunity was measured via a quantitative VZV antibody enzyme-linked immunosorbent assay assay. RESULTS: Seventy-seven patients with IBD and 12 HCs were enrolled in the study. There was no significant difference in ELISPOT counts between patients with IBD and HCs ( P = 0.54). In addition, there was also no significant difference between ELISPOT counts in immunosuppressed patients with IBD (N = 45) and HCs ( P = 0.32). We also found no correlations between ELISPOT counts and age (Spearman rho 0.014; P = 0.90). Patients with IBD had similar IgG VZV antibody levels (median 19 mIU/mL; range 0.5–218) compared with HCs (median 23.5 mIU/mL (range 4–34); P = 0.54). DISCUSSION: Young patients with IBD have equivalent cellular and humoral immunity to VZV as healthy older adults in whom HZ immunization is recommended.